The health and wellbeing of young people in sub-Saharan Africa: an under-researched area? - Kabiru Caroline W; Izugbara Chimaraoke O; Beguy Donatien (BMC, 2013)
Abstract A third of sub-Saharan Africa's (SSA) population comprises persons aged 10-24 years. These youth are growing up in a context marked by pervasive poverty, limited educational opportunities, high HIV/AIDS prevalence, widespread conflict, and weak social controls. Published research on the broad issues that affect youth health and wellbeing in SSA is limited and centers heavily on sexual and reproductive health. In this commentary, we provide a broad overview of sub-Saharan African youth, highlight research gaps with respect to youth health and wellbeing, and describe potential avenues to develop the region's research capacity on youth health and wellbeing.